Digging deeper: surface and subsoil carbon as affected by N fertilizer and tillage in continuous corn - Watts, Stuart Michael (Kansas State University, 2020)
Agricultural practices such as added C inputs and adoption of no-till are known to increase soil organic C (SOC) near the soil surface; however, it is unclear if these effects persist at depth. A long-term experiment compared the effects of two tillage systems (no-till (NT) and conventional till (CT)) and N source on SOC in Mollisol planted with continuous corn (Zea mays L.) in central Kansas. The N sources included composted organic waste (OrgF), urea (MinF), and no N fertilizer addition (Ctrl). The soil profile to a depth of 120 cm was measured for soil organic C (SOC) and N, bulk density, dissolved organic C (DOC), and δ¹³C and δ¹⁵N. Soil organic C in the soil profile was expressed as equivalent soil mass. Soil organic C and N were higher in the surface 5 cm in NT compared to CT, but the reverse was true within the 5-15 cm soil layer. Dissolved organic carbon (DOC) and the δ¹³C and δ¹⁵N signatures reflected the effects of OrgF addition to a depth of 45 cm; however, effects on soil organic C stocks were only apparent in the surface 15 cm. Twenty-two years of OrgF increased SOC stocks in the 0-15 cm layer by 18.2 Mg C ha⁻¹ over Ctrl (-1.22 Mg C ha⁻¹) and MinF (2.24 Mg C ha⁻¹). In the profile (0-60 cm), all treatments lost SOC from the 1992 baseline except for NT OrgF (0.66 Mg C ha⁻¹). Conventionally tilled OrgF lost 7.49 Mg C ha⁻¹ suggesting that NT conserved the additional C inputs more than CT. Most of the losses were in the 30 to 60 cm layers where there was a buried A horizon. Within the 30-45 cm depth, NT OrgF decreased losses of SOC (-3.80 Mg C ha⁻¹) compared to CT OrgF (-12.9 Mg C ha⁻¹). In summary, surface management effects on soil C sequestration were confined to the surface 15 cm even with additional C inputs. Although DOC and δ¹³C was elevated with OrgF in the 15-45 cm depths, this did not result in sequestered C. In these annual cropping systems, considerations need to made for deep-rooted crops and rotations to deliver C inputs into the subsoil; however, this must include no-tillage as tillage loses the benefits of additional C inputs.
Keywords: Deep soil carbon; Tillage; Nitrogen fertilizer; Soil carbon sequestration; No-till; Compost